Improving Learning Outcomes using Electronic-Crossword Puzzle Learning Media in Online Learning - Galuh Sandi; Siswandari Siswandari; Cicilia Dyah Sulistyaningrum (Budapest International Research and Critics University, 2022)
It is necessary to develop learning media as learning support during the pandemic so that students' enthusiasm for learning remains high, impacting student learning outcomes. This study aimed to determine the effect of Electronic-Crossword Puzzles (E-CP) learning media on student learning outcomes in online learning. This study was experimental research. Data collection techniques were conducted through questionnaires, observations, and interviews. The samples were 32 students from a total population of 108 students of Grade X of Yogyakarta 4 Senior High School (SMA N 4 Yogyakarta). The instrument test included validity and reliability tests. The analysis technique employed two-way Anova. The results of data analysis using the independent t-test with the help of SPSS showed a significance value of 0.000<0.05, and the comparison of the t-test shows t_count (8.973) > t_table (2.048). It means there is a difference in the average student learning outcomes in Group 1 (students given E-CP learning media) and Group 2 (students not given E-CP learning media).